Innovation in Surgery: Qualitative Analysis of the Decision-Making Process and Ethical Concerns. (December 2018) - Zarzavadjian Le Bian, Alban; Fuks, David; Costi, Renato; Cesaretti, Manuela; Bruderer, Audrey; Wind, Philippe; Smadja, Claude; Hervé, Christian
Background . Surgical innovation from surgeon's standpoint has never been scrutinized as it may lead to understand and improve surgical innovation, potentially to refine the IDEAL (Idea, Development, Exploration, Assessment, Long-term Follow-up) recommendations. Methods . A qualitative analysis was designed. A purposive expert sampling was then performed in organ transplant as it was chosen as the ideal model of surgical innovation. Interviews were designed, and main themes included the following: definition of surgical innovation, the decision-making process of surgical innovation, and ethical dilemmas. A semistructured design was designed to analyze the decision-making process, using the Forces Interaction Model. An in-depth design with open-ended questions was chosen to define surgical innovation and ethical dilemmas. Results . Interviews were performed in 2014. Participants were 7 professors of surgery: 3 in liver transplant, 2 in heart transplant, and 2 in face transplant. Saturation was reached. They demonstrated an intuitive understanding of surgical innovation. Using the Forces Interaction Model, decision leading to contemporary innovation results mainly from collegiality, when the surgeon was previously the main factor. The patient is seemingly lesser in the decision. A perfect innovative surgeon was described (with resiliency, legitimacy, and no technical restriction). Ethical conflicts were related to risk assessment and doubts regarding methodology when most participants (4/7) described ethical dilemma as being irrelevant. Conclusions . Innovation in surgery is teamwork. Therefore, it should be performed in specific specialized centers. Those centers should include Ethics and Laws department in order to integrate these concepts to innovative process. This study enables to improve the IDEAL recommendations and is a major asset in surgery.